2020
DOI: 10.1101/2020.04.03.20052860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Portable and accurate diagnostics for COVID-19: Combined use of the miniPCR thermocycler and a well-plate reader for SARS-CoV-2 virus detection

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has crudely demonstrated the need for massive and rapid diagnostics. By the first week of July, more than 10,000,000 positive cases of COVID-19 have been reported worldwide, although this number could be greatly underestimated. In the case of an epidemic emergency, the first line of response should be based on commercially available and validated resources. Here, we demonstrate the use of the miniPCR, a commercial compact and portable PCR device recently… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…The sequences of our LAMP primers are presented in Table 1. The sequences of the PCR primers (N1) have been reported elsewhere[24,53].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequences of our LAMP primers are presented in Table 1. The sequences of the PCR primers (N1) have been reported elsewhere[24,53].…”
Section: Methodsmentioning
confidence: 99%
“…To finalize our analysis, we simulated some real-time amplification experiments to compare the performance of LAMP and PCR in similar conditions (Figure 6A). To that end, we conducted amplification reactions using initial amounts of 4 × 10 4 copies of synthetic SARS-CoV2 in a commercial miniPCR cycler[24,51] (using primer set N1) and in our LAMP 3D-printed incubator (using primer set β). We added the intercalating agent, EvaGreen ® Dye, to the reaction mix at the initial time and extracted samples after 0, 7, 14, 21, 28, 35, 42, and 51 minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several publications have detailed molecular methods and medical tools to accelerate the detection process of the coronavirus responsible of COVID-19 pandemic [ 3 , 7 , 174 ]. For instance, Chu et al developed a single-step real-time reverse-transcription polymerase chain reaction (RT-qPCR) assay to detect two different regions of the viral genome [ 175 ] while González-González et al [ 176 ] found no significant differences when they compared the efficiency of a mini-PCR equipment to its lab-bench counterpart. On the other hand, the same group designed a 3D-printed incubator for a faster amplification of the COVID-19 genome using loop-mediated isothermal amplification (LAMP) reaction that is detected using qRT-PCR [ 177 ].…”
Section: Diagnostics and Biosensors For Covid-19mentioning
confidence: 99%
“…Solo se encontró un estudio que abordó los aspectos terapéuticos de la de la enfermedad y, además, aportaba, el mayor nivel de evidencia (ensayo clínico aleatorizado, doble-ciego) de todos los reportados en esta revisión (36). Cuatro investigaciones de ciencias básicas fueron publicadas en la región (37)(38)(39)(40).…”
Section: Conocimiento De La Covid-19 En Latinoaméricaunclassified